Solar PV Plant as a Replacement for Power Supply of Irrigation Water Pump - Sastradiangga, I Made Agus; Giriantari, Ida Ayu Dwi; Sukerayasa, I Wayan (International Journal of Engineering and Emerging Technology, 2020)
The southern side of Subak Babakan Yeh Kuning has an agricultural irrigation water shortage due to the dry season’s drought. In 2016, the Ministry of Public Works and Public Housing resolved that by giving diesel-powered irrigation water pump system and groundwater irrigation network, however the high operations cost resulted an abandonment of it. This study conducted a solar power plant design for submersible pumps at the southern side of Subak Babakan Yeh Kuning by calculating the amount of irrigation water needed, designing the solar power plant and the investment costs, and comparing the operations cost between the new and old system. Based on the design, the capacity of the solar power plant was set at 12,54 kWp using 33 solar module units and a 18,5 kW inverter unit. The pump could operate for 5 hours and 30 minutes on a sunny weather with a water discharge of 253 m 3 or fulfill 17,5% of water needs  for an area of 16-hectare. The investment costs of the solar power plant pump system were IDR 171.193.500. The operations cost of the new system (solar-powered) per hectare was IDR 6.495/day. Meanwhile, the operations cost of the old system (diesel-powered) per hectare was IDR 15.950/day .